The Gendered Individual in Funerary Papyri of the Ptolemaic and Roman Periods - Cole, Emily.
In the magical texts provided to Egyptians to transition to the afterlife, the mythological precedent set by the rebirth of Osiris created gendered theological principles, which remained central to funerary beliefs throughout Egyptian history. At the point of mummification, the body of the deceased, male or female, temporarily took part in the Osirian rituals and was transformed. As restrictive guidelines for the use of texts started to fall away in the Third Intermediate period, and even more so in the Graeco-Roman period, there were many new, appropriate ways to connect a funerary text to a single person. This article addresses how ancient scribes accommodated allusions and adapted religious content to the text’s owner more extensively in later periods. Rather than the basic grammatical changes found in pharaonic sources, later scribes inserted gendered mythological references and biographical material as textual alterations to create personalized documents for either gender. They creatively pushed the boundaries of individualization as far as possible, but remained within the idealized context of funerary beliefs. Instead, they differentiated male or female gender roles to accentuate the character of the deceased only where appropriate without jeopardizing access to the next life.